Review of ’The Penelope Project: An Arts-Based Odyssey to Change Elder Care’ edited by Anne Basting, Maureen Towey, and Ellie Rose - Barnes Lipscomb, Valerie (Age, Culture, Humanities: An Interdisciplinary Journal, 2020)
—